A descriptive study on the use of social networking websites and physical health profile of their users among college students in Thrissur district, Kerala - Ibrahim N., Mohammed; T., John George; Mundodan, Jenyz M.; M. P., Jini (International Journal Of Community Medicine And Public Health, 2018)
Background: The internet has become much more personal since social network sites (SNS) were introduced and embraced by the masses. Since their introduction, social networking websites have attracted millions of users, many of whom use these sites daily. Its excessive usage can influence physical health of their users. Methods: A descriptive study was conducted among students of selected colleges in Thrissur district. The subjects included 400 SNS users selected using systematic random sampling. Data was collected using a pre tested structured questionnaire. Results: The mean age of the study population was 19.13±1.09 years. Most of the subjects used Facebook along with (78%) or without (33.5%) the usage of other social networking websites. Among the subjects, 64% were daily users with 39.5% reporting 1-2 hours use per day and 29.5% reporting 2-4 hours use per day. 74% subjects reported mobile phone as method of access to SNS. The prevalence of visual problems, eyestrain, headache, appetite problems and postural pain were significantly high in daily SNS users. Conclusions: The study shows how virtual online world is interfering with their physical health. Daily SNS use had negative effects on physical health of the college students in this study.